Blockchain for Enhancing Trust in E-Government Services (Al-Mansour Journal, 2025)
This research introduces and tests a blockchain-based approach for building citizens trust in e-government services. Using the mixed-methods research design in a two-stage approach, we first conducted the expert focus groups (n=12) to generate a conceptual model of the relationship between perceived security (PS), transparency (TR), data integrity (DI), and procedural fairness (PF) with trust in service (TS), intention to adopt (AI), with governance quality (GQ) as a contextual moderator. Then we did a survey of 412 active users of public digital services and analyzed this data using PLS-SEM. The reliability and validity of the measurement model was good (alpha=.82-.91; AVE=.59-.76). The structural model accounted for 68% of TS and 61% of AI (SRMR=.056; NFI=.90). All antecedents were positively associated with TS (betaPS=.27; betaTR=.23; betaDI=.18; betaPF=.22; all p values
Keywords: Blockchain; E-Government; Trust; Governance; Smart Contracts